2021
DOI: 10.1038/s41396-021-01093-8
|View full text |Cite
|
Sign up to set email alerts
|

T6SS secretes an LPS-binding effector to recruit OMVs for exploitative competition and horizontal gene transfer

Abstract: Outer membrane vesicles (OMVs) can function as nanoscale vectors that mediate bacterial interactions in microbial communities. How bacteria recognize and recruit OMVs inter-specifically remains largely unknown, thus limiting our understanding of the complex physiological and ecological roles of OMVs. Here, we report a ligand-receptor interaction-based OMV recruitment mechanism, consisting of a type VI secretion system (T6SS)-secreted lipopolysaccharide (LPS)-binding effector TeoL and the outer membrane recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 73 publications
1
63
1
Order By: Relevance
“… 99 H3-T6SS secrete TseF to facilitate the import of the PQS-Fe 3+ complex into cells by incorporating it into OMVs with Pseudomonas quinolone signal (PQS). 100 Interestingly, it was found that the quorum sensing (QS) system plays an important role in the expression of this secretion system. In P. aeruginosa , QS differentially regulates three loci of encoding T6SS (HSI-I, HSI-II, and HSI-III) by LasR and MvfR.…”
Section: Secretion Systems An Integral Part Of Virulence Platforms An...mentioning
confidence: 99%
“… 99 H3-T6SS secrete TseF to facilitate the import of the PQS-Fe 3+ complex into cells by incorporating it into OMVs with Pseudomonas quinolone signal (PQS). 100 Interestingly, it was found that the quorum sensing (QS) system plays an important role in the expression of this secretion system. In P. aeruginosa , QS differentially regulates three loci of encoding T6SS (HSI-I, HSI-II, and HSI-III) by LasR and MvfR.…”
Section: Secretion Systems An Integral Part Of Virulence Platforms An...mentioning
confidence: 99%
“…Recently, some groups have successfully isolated human EVs by targeting specific phospholipids using Tim4 protein and annexin V ( 115 , 130 ). Similarly, anti-LPS or LPS-binding effector TeoL could be used to isolate LPS-rich OMVs ( 131 ). Additionally, some are investigating whether proteins that sense and bind to highly curved phospholipid membranes and the peptides derived from them can be used to selectively capture EVs ( 132 , 133 ).…”
Section: Evs As Molecular Biomarkers For Sepsismentioning
confidence: 99%
“…The H3-T6SSpromoters and tseF expression for iron acquisition are commonly repressed by the ferric uptake regulator (Fur) for intracellular iron homeostasis (Lin et al, 2017). In Cupriavidus necator, T6SS1 secreted TeoL preferentially in association with OMVs through interactions with LPS, which enables bacterial cells to recruit OMVs derived from different species and confers advantages to bacterial cells for iron acquisition (Li et al, 2021).…”
Section: Ironmentioning
confidence: 99%